Three-dimensional vibration suppression for an Euler–Bernoulli beam with asymmetric output constraint. Issue 7 (May 2021) - Jing, Zhe; He, Xiuyu; Liu, Zhijie; Zhang, Shuang; Kang, Wen
Abstract: A vibration control strategy is addressed for the three-dimensional vibration suppression of an Euler-Bernoulli beam (EBB) subject to asymmetric output constraints in this paper. A special piecewise barrier Lyapunov function candidate is provided to prevent the asymmetric output constraint violation, and a model-based boundary control (MBC) is developed subsequently to ensure the coupled vibration reduction. Moreover, considering the parameter uncertainties, an adaptive law is designed to estimate the uncertain parameter and to update the vibration controller. The main challenge of this work is to consider the asymmetric output constraint in a nonlinear and coupled infinite-dimensional system. Finally, numerical simulations are made to present the system performance under the proposed vibration controllers which maintain the output being restrained in the predefined scope.